Globalization and financial development in East Asian economies : panel data evidence - Law, Siong Hook; Wan Ngah, Wan Azman Saini
This study examines the role of globalization on financial development in eight East Asian economies, paying particular attention to the importance of institutions in mediating this link. Given the relatively short span of the time series data, a panel cointegration and panel Granger causality tests are employed to infer the long-run and short-run causal relationships. The heterogeneous panel cointegration test reveals that cointegration is present among globalization, institutions, financial reforms, financial development and real GDP per capita. The Granger causality results indicate that globalization has significant causal influence on institutional quality, and institutional reforms in turn facilitate and support financial development, in particular the development of banking sector in East Asia. Globalization is also found to have a favorable causal impact on stock market development without passing through institutional quality channel.